Total neoadjuvant treatment and PD-1/PD-L1 checkpoint inhibitor in locally advanced rectal cancer - Xiao, Weiwei; Luo, Huilong; Yao, Ye; Wang, Yaqin; Liu, Shuang; Sun, Rui; Chen, Gong (Frontiers in Immunology, 2023)
For local advanced rectal cancer (LARC), total neoadjuvant treatment (TNT) has shown more complete response (CR), reduced risk of distant metastasis (DM) and increase of the sphincter preservation rate. Now it is the one and only recommendation for high-risk group of LARC according to NCCN rectal cancer guideline, while it is also preferentially recommended for low-risk group of LARC. TNT is also beneficial for distant rectal cancer patients who have need for organ preservation. Even though the prognostic value of PD-L1 in the neoadjuvant chemoradiotherapy (NACRT) of LARC patients is undetermined yet, the combination of NACRT and PD-1/PD-L1 antibodies seem bring new hope for mismatch repair proficient (pMMR)/ microsatellite stable (MSS) LARC patients. Accumulating small sample sized studies have shown that combining NACRT with PD-1/PD-L1 antibody yield better short-term outcomes for pMMR/MSS LARC patients than historic data. However, ideal total dose and fractionation of radiotherapy remains one of unresolved issues in this combination setting. Thorough understanding the impact of radiotherapy on the tumor microenvironment and their interaction is needed for in-depth understanding and exquisite design of treatments combination model.